Business Strategy To Increase Competitiveness and Profitability of Premios Dessert Proposed Marketing Strategy of General Daily Pikiran Rakyat in Facing Online Media Competition for PT. Pikiran Rakyat Bandung (The Indonesian Journal of Business Administration, 2021)
The development of print media in 2020 closed several national and regional print media which caused a decrease in revenue from the advertising sector and the circulation sector. In addition, the public has many options for obtaining information. This makes PT.Pikiran Rakyat Bandung strive to provide the best service to the community by implementing a media convergence strategy. The purpose of this study was to determine and analyze the marketing strategy carried out for General Daily of Pikiran Rakyat to survive in the midst of intense competition with online media and social media. This study uses a descriptive method with a qualitative approach. Information determined purposively based on consideration of mastering the problem, having complete and honest data and providing data openly/honestly and objectively. Data analysis was carried out by systematically arranging interviews, data literature, and formulating descriptively. The results showed that the People's Mind implemented a media convergence strategy with aspects of cloning, content sharing, crossprice and crosspromotion. In dimensional cloning and content sharing, the editorial department seeks to improve news quality, design features, create various rubrics, content published in PR Print is also published in PR Online, PR Groups and packaged in digital format. Dimensions of crossprice and crosspromotion, the marketing department for newspapers and advertisements makes promotions or advertisements and their coverage can be found in PR Groups, PR Online, Mesos and PR FM. On the crossprice aspect, Advertisers can pay a package price to display their ads in either print PR or Online PR.Keywords: Marketing Strategy, Online Newspaper & Digital Reader